Identification of 10 differentially expressed and cuproptosis-related genes in immune infiltration and prognosis of thyroid carcinoma: The gene expression in TC - Yu, Weixuan; Liu, Haiping; Zhang, Yunda; Liu, Ming; Li, Weicong; Wang, Libin; Li, Dongwei (Cellular and Molecular Biology, 2024)
The association between the cuproptosis-related genes and the immune infiltration and their prognostic value in thyroid carcinoma is still unexplored. Bioinformatics analyses were performed with data obtained from the TCGA dataset. The aberrantly expressed genes were selected. KEGG and GO analyses were conducted to explore the enriched pathways of the up-regulated or down-regulated genes in thyroid carcinoma. Totally 1495 genes were differentially expressed (691 up-regulated, 804 down-regulated) in thyroid carcinoma (p<0.05). The 10 cuproptosis-related RNAs (DLD, LIAS, LIPT1, FDX1, DLAT, MTF1, PDHA1, CDKN2A, GLS and PDHB) were also demonstrated to be aberrantly expressed in thyroid carcinoma patients tissues. FDX1 expression was correlated with the overall survival in thyroid carcinoma patients (HR=0.4995, 95% CI: 0.2688-0.9285, p=0.0282). Further multivariate cox regression analysis revealed that DLD (HR=24.8869, 95% CI: 4.48772-138.01181, p=0.00024), and LIAS (HR=7.74092, 95% CI: 1.12194-53.40898, p=0.03783) were associated with the survival of thyroid carcinoma patients. The immune infiltration analysis demonstrated that significant correlation between the 10 cuproptosis-related genes and immune infiltration in thyroid carcinoma (p<0.01). We presented the expression profiles of dysregulated genes in thyroid carcinoma. The findings of our study highlighted the potential of cuproptosis-related genes as prognostic biomarkers for thyroid carcinoma.